Rancang Bangun Sistem Informasi Pengolahan Data SPT Dan SPPD Berbasis Web Pada Kantor Sekretariat Dewan Kawasan Perdagangan Bebas Dan Pelabuhan Bebas Bintan Dan Karimun - Danandjaya Saputra; Tedy Cahyadi (Jurnal Bangkit Indonesia, 2022)
The preparation of SPT and SPPD documents experiences an intensity level of official travel activities carried out by the Regional Council Secretariat employees can be said to be frequent, but even though this is the case at the Regional Council Secretariat office there is no database that stores SPPD and SPT data, so the handling of SPPD and SPT is still just or it is called manual, apart from requiring a lot of manpower, it is also not well systemed. Manual manufacturing is often encountered with many errors, besides being wasteful of time, wasteful of material and wasteful of energy. To overcome this situation, it is necessary to build a web-based data processing system regarding SPPD and SPT that can help the performance of the Regional Council Secretariat employees more effectively and efficiently. This system is built using the PHP and MySQL programming languages as the database, as well as the software modeling method using UML. the existence of a Web-Based SPT and SPPD Data Processing Information System at the Secretariat Office of the Free Trade Zone Council and Free Port of Bintan and Karimun can assist employees in dealing with the above problems.